2016
DOI: 10.1007/s10461-016-1627-z
|View full text |Cite
|
Sign up to set email alerts
|

Values and Preferences on the Use of Oral Pre-exposure Prophylaxis (PrEP) for HIV Prevention Among Multiple Populations: A Systematic Review of the Literature

Abstract: Daily oral pre-exposure prophylaxis (PrEP) is the use of antiretroviral drugs by HIV-negative people to prevent HIV infection. WHO released new guidelines in 2015 recommending PrEP for all populations at substantial risk of HIV infection. To prepare these guidelines, we conducted a systematic review of values and preferences among populations that might benefit from PrEP, women, heterosexual men, young women and adolescent girls, female sex workers, serodiscordant couples, transgender people and people who inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 73 publications
(68 reference statements)
10
115
4
1
Order By: Relevance
“…Finally, the PrEP users who participated in our study identified an important role for peer support in initiating and continuing PrEP use and expressed significant enthusiasm for sharing their own experiences. This finding adds to previous research demonstrating that peer support or approval can facilitate PrEP uptake (Hannaford et al, 2018;Koechlin et al, 2017). While peer-to-peer or patient navigation interventions are recommended for promoting retention in HIV care, more research is needed to explore how similar interventions may be used to support PrEP use.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the PrEP users who participated in our study identified an important role for peer support in initiating and continuing PrEP use and expressed significant enthusiasm for sharing their own experiences. This finding adds to previous research demonstrating that peer support or approval can facilitate PrEP uptake (Hannaford et al, 2018;Koechlin et al, 2017). While peer-to-peer or patient navigation interventions are recommended for promoting retention in HIV care, more research is needed to explore how similar interventions may be used to support PrEP use.…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, three other papers noted that risk behaviour did not change over time among participants actually using PrEP including migrant workers and female partners, MSM, FSW and serodiscordant couples [36,42,43]. It should also be noted that two systematic reviews also have shown no significant changes in behaviour among PrEP users [1,17].…”
Section: Realities and Compensationmentioning
confidence: 99%
“…A systematic review described strong interest and support for PrEP use among many younger populations at risk of HIV infection including adolescent girls and young women, youth who identify as transgender, and, to a lesser extent, youth who inject drugs [26]. Two recent mixed-method studies of MSM, one in Kenya and one in the UK, found that younger men were more willing than older MSM to take daily oral PrEP [27, 28].…”
Section: Other Considerations Regarding Prep For Youthmentioning
confidence: 99%